The synergistic effects of oxygenated additives on papaya biodiesel binary and ternary blends. (15th November 2019) - Anwar, Mohammad; Rasul, Mohammad G.; Ashwath, Nanjappa
Graphical abstractat: Experimental setup for engine testing with PSO binary and ternary blends. Abstract: In this study, engine performance, exhaust emissions and combustion behaviour of a four-cylinder, four stroke indirect injection diesel engine was tested using papaya seed oil (PSO) biodiesel binary and ternary blends. The results were compared with those of diesel fuel under a range of engine speeds from 1200 rpm to 2400 rpm, and for different engine load conditions of 25% to 100%. The PSO biodiesel of 20% v/v with 80% v/v diesel was considered as the binary blend (P20). Two ternary fuel blends of 5% v/v of oxygenated additives (diglyme and n-butanol) with P20 biodiesel and 75% v/v of diesel which are referred to as P20DG5 (diglyme) and P20BT5 (n-butanol). Another ternary blend made of 10% v/v of PSO biodiesel with 80% v/v diesel and 10% v/v stone fruit oil (SFO) biodiesel referred to as PSFO20 is used to compare the overall results. The average brake specific fuel consumption (BSFC) value and brake thermal efficiency (BTE) of P20DG5 was found to be 0.50% lower and 3.30% higher than diesel respectively. The P20DG5 produced about 0.64% less NOx emissions compared with diesel and had the shortest ignition delay period. As a conclusion, P20DG5 proved to be an excellent choice for mitigating the environmental problems without compromising the engine performance and enhanced better combustion. The P20DG5 ternary blend is recommended to use in diesel engine without any need for physical modification.